THE SOCIO-DEMOGRAPHIC PROFILE OF INFERTILE COUPLES AND CAUSES OF INFERTILITY IN MOLDOVA: THE CASE STUDY - Ciubotaru, Victoria (Economy and Sociology, 2023)
The present study aims to analyze infertile married couples’ demographic and social characteristics to understand the need for policy interventions to prevent, diagnose, and treat infertility in Moldova. The study provides information about couples facing the problem of infertility, its causes and risk factors. The study is based on the analysis of medical documentation from the files submitted by infertile couples, during 2017-2021, to the Commission for the Evaluation of Insured Couples. In addition to the documentary analysis, the individual interviews were followed during the Commission meetings with the 244 couples whose files submitted met all the conditions stipulated in the normative acts of the Ministry of Health. The study results showed that the primary beneficiaries of in vitro fertilization are people aged 30-39 who live in urban areas, usually in the capital city of Chisinau. Married couples from rural areas are less likely to use specialized services, which is associated with their low level of information and the low financial availability of this service for rural residents. Among the main infertility factors, the tubal factor was detected, which determined more than half of the cases of infertility among the studied couples. Based on the research, some policy recommendations are formulated, such as improving the information system and databases, increasing access to services and the quality of the services offered, and introducing measures to prevent infertility.